A Novel Sol–Gel Method for Large‐Scale Production of Nanopowders: Preparation of Li1.5Al0.5Ti1.5(PO4)3 as an Example. Issue 2 (16th October 2015) - Ma, Qianli; Xu, Qi; Tsai, Chih‐Long; Tietz, Frank; Guillon, Olivier
Abstract : Sol–gel synthesis is an extensively used method for the preparation of nanopowders. However, complicated or expensive precursors, and the necessity of using organic solvent and/or heat assistance limit the method to laboratory‐scaled level. An aqueous‐based sol–gel method with spontaneous sol and gel formation is developed in this study. It can be applied on a large scale to synthesize compounds with Ti 4+ and PO4 3− as major components with low cost. Al‐substituted LiTi2 (PO4 )3 (LATP) has been widely investigated as a promising candidate for solid electrolyte in Li‐ion or Li‐air batteries. Major challenges such as unsatisfactory phase purity, low sintering activity, and high production costs are faced during the fabrication of LATP. In this study, as a sample application, Li1.5 Al0.5 Ti1.5 (PO4 )3 (LATP05) is conveniently prepared on a large scale by the novel sol–gel method with high phase purity, active densification behavior and high conductivity.